Antithrombin III and its Interactions with Heparin - Rosenberg, R.D.; Jordan, I.R.; Armand, G.; Lam, L.H.; Beeler, D.L. (Thrombosis and Haemostasis, 1977)
Heparin functions as an anticoagulant by binding to antithrombin and accelerating the rate at which this protein inhibitor inactivates the serine proteases of the hemostatic system. Despite considerable effort, the precise relationship between the structure of this mucopolysaccharide and its biologic properties has remained elusive.We have provided the first evidence that only a small portion of a given heparin preparation binds tightly to antithrombin and is responsible for the bulk of anticoagulant activity. The major fraction of these products has very little anticoagulant effect.In our presentation, we shall discuss optimal techniques for fractionating heparin into “highly active” and “relatively inactive” molecular forms.Furthermore, we shall consider the distinctive interactions of these two types of mucopolysaccharides with antithrombin, thrombin and other hemostatis system components.Lastly, we shall provide evidence that several structural differences exist between these two forms of heparin.